Análise e simulação dos limites de operação de um d-statcom operando em redes de distribuição com elevada impedância - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The increase in the demand for electric power due to the growth of the industrial and good sectors and services, as well as of the residential class, imply the need for the expansion and modernization of the electric sector. The distribution of electric energy, the segment responsible for supplying the electric power supply service to the different classes of consumers, has as one of its obligations to maintain not only the voltage levels and the power factor within suitable bands, but also comply with the regulations imposed by Module 8 of PRODIST. Voltage levels outside the appropriate limits compromise the operation of various electronic equipment, many of which are sensitive to slight voltage variations and other forms of interference. The possibility of using new equipment capable of controlling the voltage level directly at the network connection point became real from the advances in the studies of second generation Flexible Alternating Current Transmission System (FACTS) which employ greater use of self-commutated semiconductor keys. Of these equipments, it is possible to emphasize the Static Compensator of Reactive Power in Distribution Networks (DSTATCOM), which through its structures presents/displays good potential for the voltage level control and power factor correction at the point of common coupling (PCC), using the active and reactive power control to be inserted or absorbed from the distribution network. The active power injection capacity can be attributed to the connection of an active power source to the dc voltage bus, transforming the D-STATCOM in a Distributed Generation (DG). Thus, another important point to be analyzed in the compensators is their power transfer capacity. For this, it is important to carry out the studies of their power capacity curves by means of the equation of the expressions of active and reactive power. In order to evaluate both the voltage level and the compensator behavior, a 13.8 kV/0.22 kV six-bus distribution network is implemented in the OpenDSS® software, in which the voltage profiles were analysed for different active and reactive (capacitive and inductive) powers where the compensator is connected to the bars five or six. The best cases where the voltage level remained within the range regulated by ANEEL were those in which the compensator carried out the injection only of active power or reactive power (capacitive). The worst cases were attributed to the purely inductive compensation, where the voltage levels diverged from the ideal range. With regard to the operation with current limitation, D-STATCOM presented a reduction of the injection of active and reactive powers.
Keywords: Engenharia elétrica; Conversores estáticos; Compensador estático de reativos para distribuição; Injeção de potência; Electrical engineering; Static converters; Distribution reactive power static compensator; Power injection; CNPQ::ENGENHARIAS